A new species of Alipumilio Shannon (Diptera, Syrphidae) found in association with the exudate resin of Schinus terebinthifolius Raddi (Anacardiaceae) - Morales, Mírian Nunes; Massardo, Darli; Moreira, Gilson R. P.; Thompson, F. Christian (Zootaxa, 2009)
The adult stage of a new species of flower fly, Alipumilio athesphatus Thompson (Diptera, Syrphidae) is described. The gross morphology and external integumentary features of the egg, third-instar larva and pupa are also presented. All immature stages were found in association with the exudate resin of Schinus terebinthifolius Raddi (Anacardiaceae) in Porto Alegre, Rio Grande do Sul State, Brazil.